CASUAL FACTORS AFFECTING TO MARKET READINESS ASSESSMENT AND BUSINESS PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES (SMEs) IN THAILAND - Guergoson, Khunkorn; U-on, Vichit (Journal of Graduate School of Commerce-Burapha Review, 2020)
The objectives of this research were to (1) study factors of Market Readiness Assessment on Business Performance of Thailand’s Small and Middle-Sized Enterprises (SMEs) (2) to examine factors on Market Readiness Assessment of Thailand’s SMEs entrepreneurs (3) to build up models of SMEs entrepreneurs’ Market Readiness Assessment. The research was a mix methods research in form of an explanatory research. Concepts and theories were reviewed to define conceptual framework and create questionnaires as a research instrument for data collection. Date was collected from Five hundred and four persons of sampling group including SMEs in the manufacturing sector in Bangkok. Five variables, including Market Readiness Assessment, Innovation, Organization Supportiveness, Information Technology and Business Performance were studied. Research instruments were questionnaire and data analysis by LISREL program as statistical technique of Structural Modeling: SEM. Findings from quantitative research were summarized as statistical model and in-depth interview to affirm the findings. According to the findings, Innovation gave direct impact on Market Readiness Assessment and Business Performance. Organization Supportiveness had a direct influence in Market Readiness Assessment and Business Performance. Information Technology gave direct impact on Market Readiness Assessment and Business Performance. Market Readiness Assessment gave direct impact on Business Performance which was an influence with positive meaning.